Simulation-Based Project Learning in ESP: The Effectiveness of Crewpers for Vocational Journalism Education - Sumira; Febriansyah, Gema; Miladiyenti, Fithratul; Wahyuni, Nini; Laily, Hamidah Izzatu (Universitas Hamzanwadi, 2025)
Preparing students for professional communication in English for Journalism requires more than linguistic accuracy; it demands authentic, workplace-oriented learning environments that replicate editorial processes. Despite the increasing use of project-based learning (PBL) in English for Specific Purposes (ESP), few studies have examined digital newsroom simulations aligned with vocational “teaching factory” models. This study evaluates the effectiveness of Crewpers, a student-developed digital journalism platform designed as an authentic newsroom simulation, in enhancing vocational English for Journalism instruction. A quasi-experimental one-group pretest–posttest design was employed with 16 students enrolled in the D4 English for Business and Professional Communication program at a public polytechnic in Indonesia. Using a validated 16-item questionnaire, student perceptions were measured across four dimensions: critical thinking, collaboration, journalistic production, and communication. Paired-sample t-test results revealed statistically significant improvements in all dimensions (p < .001), with the largest gains observed in journalistic production, where students reported greater confidence in producing publishable news content. Students also highlighted features such as real-time editorial feedback, role distribution, and public publishing as central to their learning gains. These findings suggest that Crewpers effectively bridges ESP instruction with professional performance tasks, offering a replicable model of simulation-based pedagogy for vocational contexts. While limited by sample size and reliance on self-reported data, this study underscores the pedagogical value of integrating digital newsroom platforms into ESP and recommends future research using mixed-method designs to assess long-term impacts on writing quality and professional readiness.